Art in an Expanded Field: Wittgenstein and Aesthetics - Carroll, Nöel (The Nordic Journal of Aesthetics, 2012)
This article reviews the various ways in which the later writings of Ludwig Wittgenstein have been employed to address the question “What is Art?”. These include the family resemblance model, the cluster concept model and the form of life model. The article defends a version of the form of life approach. Also, addressed the charge that it would have been more profitable had aestheticians explored what Wittgenstein actually said about art instead of trying to extrapolate from his writings an approach to what Nigel Warburton calls the art question.